The Advantages of the Dynamic Purchasing System in the Context of the Bulgarian Reality - Pavlova, Miglena (UNWE Yearbook, 2021)
In the past few years, Bulgaria has made significant progress with a comprehensive reform of the public procurement sector. One of the main directions is the development of e-procurement. The introduction of e-procurement has allowed the use of procurement techniques that have not been widely used so far. One of these methods is the Dynamic Purchasing System (DPS). It is an entirely electronic process, the potential of which is yet to be unleashed. This method is part of the development and implementation of the Centralised Automated Information System“Electronic Public Procurement” (Cais EPP).